Understanding the foundation: the state of generalist search education in library schools as related to the needs of expert searchers in medical libraries - Nicholson, Scott (Medical Library Association, 2005)
Purpose: The paper explores the current state of generalist search education in library schools and considers that foundation in respect to the Medical Library Association's statement on expert searching. Setting/Subjects: Syllabi from courses with significant searching components were examined from ten of the top library schools, as determined by the U.S. News & World Report rankings. Methodology: Mixed methods were used, but primarily quantitative bibliometric methods were used. Results: The educational focus in these searching components was on understanding the generalist searching resources and typical users and on performing a reflective search through application of search strategies, controlled vocabulary, and logic appropriate to the search tool. There is a growing emphasis on Web-based search tools and a movement away from traditional set-based searching and toward free-text search strategies. While a core set of authors is used in these courses, no core set of readings is used. Discussion/Conclusion: While library schools provide a strong foundation, future medical librarians still need to take courses that introduce them to the resources, settings, and users associated with medical libraries. In addition, as more emphasis is placed on Web-based search tools and free-text searching, instructors of the specialist medical informatics courses will need to focus on teaching traditional search methods appropriate for common tools in the medical domain.